DIALOGUE AS AN INSTRUMENT OF PEDAGOGICAL RESEARCH - Andrey V. Korzhuev; Iliya I. Khersonskiy; Albina R. Sadykova (Высшее образование в России)
The article focuses on the peculiarities of pedagogical knowledge in the context of its representation in a dialogue format, among them are: nonstability of terminological apparatus; plurality of interpretation of main positions and terms; cognitive barriers; inefficient patterns of thinking; methodological problems related to the difficulties of transition from general theoretical propositions to practical recommendations. The authors dwell on the informational, reflective, and constructive aspects of a dialogue, show interdependence between these aspects. Also the paper views polylogue as a scientific communication strategy in educational research community.